Answer:
[tex]y=\frac{1}{25}x-\frac{31}{25}[/tex]
Step-by-step explanation:
[tex]y=-25x-5[/tex]
You can get the gradient of the line perpendicular to this as you know the products of their gradients will be -1.
[tex]-25*m_{perpendicular}=-1\\m_{perpendicular}=\frac{1}{25}[/tex]
We have a gradient, and a point (6, 1), so we can now substitute our known values into the line equation.
[tex](y-y_0)=m(x-x_0)[/tex]
[tex]y-1=\frac{1}{25} (x-6)[/tex]
Rearrange for y and collect terms.
[tex]y=\frac{1}{25}x-\frac{6}{25}-1\\\\y=\frac{1}{25}x-\frac{31}{25}[/tex]